Banks’ Profitability and Extent of Their Employee Outlay Nexus - An Indian Perspective - Mukherjee, Sovik (Indian Journal of Finance, 2019)
This paper made an attempt to scrutinize the causal liaison between yield performance of Indian banks, being measured through profit per employee, business per employee, return on assets (excluding co-operative banks, regional rural banks, and foreign banks having their representative offices in India), and the percentage of expenditure incurred towards salary and compensation paid to its employees. I used panel data approach for the purpose of examining this relation across different categories of banks, that is, public sector banks and private sector banks for a period of 13 years starting from the year 2005 to 2017. An empirical model was developed to illustrate that banks’ profitability does not necessarily translate into an optimal rewardable employees’ benefit and compensation policy, more so for private sector banks considered here in this study - a paradoxical proposition of sorts.